IMPACT OF DECENTRALIZATION ON THE INVESTMENT ATTRACTIVENESS OF EU COUNTRIES AND UKRAINE - Kiriienko, S. (Sworld-Us Conference proceedings, 2025)
The thesis is devoted to the study of the impact of the processes of decentralization of power on the investment attractiveness of the EU countries and Ukraine, for which modeling was carried out using three indicators: the indicator of consolidated publi